Comparison of Electroanatomical Mapping Systems: Accuracy in Left Atrial Mapping. Issue 5 (25th February 2013) - HEIST, E. KEVIN; PERNA, FRANCESCO; CHALHOUB, FADI; DANIK, STEPHAN; BARRETT, CONOR; HOUGHTALING, CHRISTOPHER; TONDO, CLAUDIO; MAHAPATRA, SRIJOY; RUSKIN, JEREMY; MANSOUR, MOUSSA
<x xml:space="preserve">Abstract</x> Background Current 3D mapping systems have difficulty rendering complex cardiac structures. Different electroanatomical mapping software has been recently developed which uses a mathematical algorithm to improve interpolation between mapped points and delineation of closely spaced structures. This study tested the feasibility and accuracy of this software in comparison to traditional software. Methods In vivo 3D impedance‐based mapping using a multielectrode catheter with a single geometry point cloud was performed in the left atria and pulmonary veins (PV) in 23 patients undergoing catheter ablation for atrial fibrillation. The maps were analyzed with traditional (NavX, St. Jude Medical, Minnetonka, MN, USA), either with or without multichamber mapping versus St. Jude OneModel™ software and dimensions of cardiac chambers in human studies were compared to preprocedural computed tomographic (CT) or magnetic resonance (MR) scans to determine the relative accuracy of the maps. Results Maps created by the OneModel software provided greater detail of complex cardiac structures compared to traditional software. Comparison of the left atrial/pulmonary vein electroanatomical maps with the CT and MR scans as reference standard demonstrated significantly less error in measurement of all PV ostial long‐ and short‐axis dimensions, inter‐PV distance, and ridge width (left PV to left atrial appendage) with the OneModel versus traditional software (P < 0.001 for all dimensions measured). Conclusions The OneModel software produces maps that are more accurate in rendering complex cardiac structures compared to traditional software.